An investigation of the failure of a 1/4" ball valve. (June 2019) - Moses, Daniel; Haider, Ghulam; Henshaw, John
Abstract: This paper describes the failure analysis of a 1/4 in. brass ball valve that operated extensively in a partially opened state. The valve showed signs of extreme erosion and corrosion damage and was eventually replaced due to leakage from the valve body. The failure mechanisms observed are a result of improper valve selection and/or operational error. Summary of failure causes: The valve was left partially open for prolonged throttling applications. This resulted in extensive fluid and cavitation erosion. Abrasive particles (sand) became embedded in the seals. These particles scratched grooves into the ball surface and prevented proper sealing. Saltwater weakened the brass components through a de-alloying corrosion process. Corrosion was further expedited by cavitation. Ball valves are not intended for continuous throttling operations in harsh environments. Use of a globe type valve is recommended for controlling fluid flow rate in this application. Highlights: A ball valve was left partially open for prolonged throttling applications. Severe fluid and cavitation erosion damaged the valve ball, seals, and body. Abrasive particles became embedded in the seals causing scratches on the valve ball. Saltwater weakened the brass components through a de-alloying corrosion process. Ball valves are not recommended for controlling fluid flowrates via throttling.